(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
The objective of this paper is to evaluate the performance of Argentina in exports of goods. Its purpose is to build a diagnosis based on systematic criteria in order to characterize the pro- ducts exported by Argentina and also to discuss possibilities for the future. The main part of the analysis is based on indexes of product differentiation and technological content of exports that are computed for a sample of countries. Based on the content of product differentiation prevalent worldwide, the different products are defined as differentiated, with potential for differentiation, and homogeneous. One of the main conclusions of the paper is that a large part of Argentine exports belongs to the group of products with potential for differentiation, and that both product differentiation and diversification of export destinations could increase in order to raise total exported value, in particular in products related to the primary sector such as processed oils, meat and poultry, fruits and vegetables, other processed foods and beverages, and also chemicals and clothing.